1997
DOI: 10.1007/bf01007703
|View full text |Cite
|
Sign up to set email alerts
|

Endochitinase and ?-1,3-glucanase genes are developmentally regulated during somatic embryogenesis inPicea glauca

Abstract: Two cDNAs isolated from white spruce [Picea glauca (Moench) Voss] somatic embryos, are predicted to encode a basic class IV chitinase and a beta-1,3-glucanase, respectively corresponding to genes PgChi-1 and PgGlu-1. Each represents a multigene family in spruce. Transcripts homologous to PgChi-1 or PgGlu-1 genes were highly abundant in embryogenic tissues and gradually decreased after tissues were placed on abscisic acid-containing maturation medium, with lowest abundance in globular embryos. Transcripts relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 33 publications
3
38
0
Order By: Relevance
“…PaChi4 is similar to the basic class IV chitinases PgChi-1, Chia4-Pa1.1, and Chia4-Pa1.3, which are developmentally regulated during somatic embryogenesis in white spruce and Norway spruce, respectively (9,39). Based on the expression patterns, Wiweger et al (39) proposed that Chia4-Pa1.1 and Chia4-Pa1.3 promote somatic embryogenesis in Norway spruce, possibly by stimulating programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PaChi4 is similar to the basic class IV chitinases PgChi-1, Chia4-Pa1.1, and Chia4-Pa1.3, which are developmentally regulated during somatic embryogenesis in white spruce and Norway spruce, respectively (9,39). Based on the expression patterns, Wiweger et al (39) proposed that Chia4-Pa1.1 and Chia4-Pa1.3 promote somatic embryogenesis in Norway spruce, possibly by stimulating programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…PaChi4 cDNA was 96 to 97% identical to the class IV chitinase PgChi-1 from Picea glauca (GenBank L42467) (9) and to the class IV chitinases Chia4-Pa1.3 (GenBank AY270016) and Chia4-Pa1.1 (GenBank AY270017), which may promote programmed cell death in embryogenic tissue cultures of Norway spruce (39). The deduced amino acid sequence of PaChi4 differed at five or more amino acid positions from the Chia4-Pa (39) chitinases.…”
Section: Methodsmentioning
confidence: 99%
“…Endochitinases are constitutively expressed in several organs of healthy plants (Samac et al, 1990;Beerhues and Kombrink, 1994;Robinson et al, 1997;Yeboah et al, 1998). However, the modulation of chitinase expression was observed in response to Nod factors during the nodulation process (Staehelin et al 1994 and1995;Goormachtig et al, 1998), as well as in adverse conditions, suggesting that these enzymes are involved in plant defence responses (Samac and Shah, 1991;Margis-Pinheiro et al, 1993;Beerhues and Kombrink, 1994;Büchter et al, 1997;Busam et al, 1997;Dong and Dunstan, 1997;Yu et al, 1998;Ancillo et al, 1999). It has also been demonstrated that plant endochitinases expression is spatially and temporally regulated during plant development processes such as somatic embryogeneses (de Jong et al, 1992 and.…”
Section: Introductionmentioning
confidence: 99%
“…In carrots, the presence of EP3 chitinase increased the number of globular embryos of ts11 mutants in non-permissive temperature conditions and also promoted the transition from the globular to heart-shape stage (de Jong et al, 1992 and. In Picea glauca, a chitinase gene is also activated during maturation of somatic embryos (Dong and Dunstan, 1997). …”
Section: Introductionmentioning
confidence: 99%
“…While most previously characterized chitinases from cluster 1/class IV have been implicated in embryogenesis (Dong and Dunstan 1997;Passarinho et al 2001;Wiweger et al 2003) and pest or pathogen responses (Stein et al 2006; SP signal peptide, CBD chitin binding domain, GH glycosyl hydrolase catalytic domain, CTE carboxy-terminal extension. Zheng et al 2006;Little et al 2007;Pré et al 2008;Islam et al 2010), some cluster 1/class IV chitinases have been implicated in abiotic stress responses, including cold acclimation (Gong et al 2001;Oono et al 2006;Swindell 2006).…”
Section: Freezing Acclimationmentioning
confidence: 99%